The Effectiveness of Using Chard Media and Peer Tutors Through Direct Teaching Hydrobiology Online Lectures - Kasman Arifin; Safilu Safilu; Jahidin Jahidin; Murni Sabilu; Damhuri Damhuri; Ahdiat Agriansyah (STAI Hubbulwathan Duri, 2022)
This study aims to obtain empirical information about the effectiveness of using media charts and peer tutors in hydrobiology on-line lectures. The study used an experimental method with a randomized control-group pretest-posttest design. The students participating in the Hydrobiology course in the odd semester 2020/2021, with a total of 58 people, were divided into two classes, namely, class A and class B. Before the experiment, a pretest was conducted with the basic concepts of Hydrobiology to be taught. The results of the pretest scores were analyzed and the differences were interpreted using t-test statistics, and the results showed that there was no significant difference in the pretest scores between class A and B (significance value 0.359 = 0.05). The results showed that the use of chard media and peer tutoring through direct on-line lecture teaching (treatment group), was effectively used to improve learning achievement (N-gain) compared to classes that used group discussions (control group), with indicators: N The total gain in the treatment class was higher than the N-gain in the control group. The learning management is also explained